Pengaruh Kualitas Sistem Informasi Akuntansi Dan Dukungan Organisasi Terhadap Kinerja Individu Dengan Kepuasan Pengguna Sebagai Variabel Intervening (Studi Pada Koperasi Di Lampug Selatan) - Irwandi Irwandi; Evi Yuniarti (Jurnal Akuntansi dan Keuangan, 2023)
This research is primarily to analyze the quality of accounting information systems, organizational support, and user satisfaction on individual performance either directly or through user satisfaction as an intervening variable. The research was conducted on active cooperatives in the South Lampung region and data were collected by distributing questionnaires to 76 cooperatives as samples. Samples were taken at random (simple random sampling) using the slovin formula with an error tolerance of 10%. The analytical method is used in two ways, namely descriptive statistical analysis and path analysis using SmartPLS-4 primarily to measure and analyze direct and indirect effects.The results of the study concluded that the variable quality of accounting information systems, organizational support, and user satisfaction has a significant effect on individual performance both directly and through the variable user satisfaction as mediation. However, organizational support has a significant effect on individual performance greater than the variable quality of accounting information systems and user satisfaction in influencing individual performance.